Correlation between initial SiO2/Al2O3, Na2O/Al2O3, Na2O/SiO2 and H2O/Na2O ratios on phase and microstructure of reaction products of metakaolin-rice husk ash geopolymer. (30th November 2019) - Juengsuwattananon, K.; Winnefeld, F.; Chindaprasirt, P.; Pimraksa, K.
Highlights: Initial chemical compositions of metakaolin (MK) and rice husk ash (RHA) were varied to produce geopolymer samples. The observed initial chemical compositions comprised of SiO2 /Al2 O3, Na2 O/Al2 O3, Na2 O/SiO2 and H2 O/ Na2 O ratios. The initial compositions significantly correlated with phase and microstructure of geopolymerization products. The initial compositions that preferred the formation of zeolitic structures provided low strength materials. In contrast, the compositions that preferred the formation of geopolymeric structures provided high strength materials. Abstract: Phase evolution and microstructure development of metakaolin-rice husk ash geopolymer have been investigated. The initial molar ratios of SiO2 /Al2 O3 were designed in the range of 2.0–7.0 with Na2 O/Al2 O3 ratios of 0.6–1.6, Na2 O/SiO2 of 0.20–0.72 and H2 O/Na2 O of 10.0–20.0. The specimens were cured at 30 °C for 1–90 days prior to characterization of phase and microstructure as well as mechanical properties. The designed molar ratios were found to correlate with phase and microstructure of reaction products related to their compressive properties. Various zeolite types (sodalite, zeolite A, zeolite Y, zeolite X and faujasite) were prominently observed in samples containing low initial molar ratios of SiO2 /Al2 O3 (2.0–2.5) with Na2 O/Al2 O3  ≥ 1.0 and H2 O/Na2 O in the range of 10.0–20.0. These low SiO2 /Al2 O3 ratios provided low strength geopolymer. Formation of geopolymeric structures was established in samples containing higher initial molar ratio of SiO2 /Al2 O3 (3.0–4.0) with Na2 O/Al2 O3 ratio of 1.0 and H2 O/Na2 O ratios in the range of 10.0–15.0. The highest strength was achieved when initial molar ratios of SiO2 /Al2 O3, Na2 O/Al2 O3 and H2 O/Na2 O were 4.0, 1.0 and 10.0, respectively. When the initial molar ratios of SiO2 /Al2 O3 increased to 6.0–7.0 with Na2 O/Al2 O3 ratios of 1.0–1.6 and H2 O/Na2 O ratios of 10.0–15.0, sodium bicarbonate compounds and unreacted raw materials were observed within the geopolymeric structures. Correlation of phase structures of reaction products with different starting chemical compositions were evaluated and revealed in a ternary composition diagram.